"The freak of nature": on Erich Fromm’s Vindication of binomial sexuality and the potentials of the "homosexual deviation" - Bauer, J. Edgar (Journal of homosexuality, 2017)
As a Freudian revisionist and neo-Marxist, Erich Fromm (1900-1980) lessened the import of sexuality in the individual psyche but stressed the role played by the sex differential in the distribution of power throughout history and in the post-patriarchal form of matriarchy he envisioned. Seeking to reinforce the male/female divide and heteronormativity, Fromm outlined a “New Science of Man” that readily ignored not only the challenges posed to binary sexuality by post-Darwinian critical sexologies, but also the same-sex complexities evinced by key figures of his own cultural pantheon. Regardless of his declared pursuits, however, Fromm at times expressed insights suitable to undermine the cogency of his most cherished sexual convictions. As a tool for uncovering “indubitable commonsensical axioms” as sources of alienation, Fromm’s conception of “idology” challenges his own sanction of sexual binarity and heterosexuality, thus facilitating an understanding of the individual’s sexual difference as a unique modulation of male/female intermediariness.
Online veröffentlicht: 11. November 2016
Gesehen am 04.08.2021